Pengembangan Produk Kelapa Sawit Merah Sebagai Sumber Pangan Fungsional dan Nutrasetikal - Indra Lasmana Tarigan; Nelson; Nuralang; Hertanti Dwi Ananda (Balitbangda Provinsi Jambi, 2022)
The utilization of palm oil products in Indonesia is still limited to the production of crude palm oil (CPO) and food products, while palm oil derivative products such as red palm oil (RPO) have not been a concern. RPO consists of palmitate, -tocopherol, oleic, -tocotrienols, linoleate, carotene, -tocotrienol, and -tocotrienol compounds, these compounds act like vitamins and antioxidants. The aim of this article is to examine the potential for developing red palm oil-based products as functional and nutraceutical food products. This article is a review related to palm oil and its derivatives starting from its potential, content of chemical compounds, potential as food and nutraceutical, as well as several processing technologies. We access these articles from various primary sources, especially from journal websites. RPO is a derivative product of CPO processing. RPO has a good nutritional value such as carotene, tocopherol, ticopherol, and tocotrienols. RPO development technology is carried out by adding probiotics and encapsulation technology as functional and nutraceutical food.